2019
DOI: 10.17582/journal.aavs/2019/7.2.122.130
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Characterization of Silver Nanoparticles by Silybum marianum (silymarin) Fruit Extract

Abstract: This study was carried out to synthesis of silver nanoparticles (AgNPs) by using Silybummarianum fruit extract which is very simple and eco-friendly method. The separation of this nanoparticle was performed by centrifugation while the identification was by UV-Visible spectroscopy, X-ray diffraction, Fourier Transmission Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM) methods. Reduction of the Ag+ to Ag0 during exposure to the S. marianum fruit extract was followed by color change of the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…The colour was fully yellowish-brown ( Figure 2 (c)) after 24 h of incubation. The colour changes in the AgNPs solution was attributed to the excitation of surface Plasmon resonance (SPR), which indicates that bio-reduction of Ag + to AgNPs has confirmed the biosynthesis of AgNPs ( Ayad et al., 2018 ). Reduction of Ag + to AgNPs by the crude extract of M. moribidii occurred faster than studies of AgNPs synthesis using the crude extract of different polychaete species by Singh et al.…”
Section: Resultsmentioning
confidence: 99%
“…The colour was fully yellowish-brown ( Figure 2 (c)) after 24 h of incubation. The colour changes in the AgNPs solution was attributed to the excitation of surface Plasmon resonance (SPR), which indicates that bio-reduction of Ag + to AgNPs has confirmed the biosynthesis of AgNPs ( Ayad et al., 2018 ). Reduction of Ag + to AgNPs by the crude extract of M. moribidii occurred faster than studies of AgNPs synthesis using the crude extract of different polychaete species by Singh et al.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristic absorbance peak of AgNPs is between 400 and 450 nm. If the peak raises above 450 nm, indicates aggregation or precipitation resulting particle with large size but if peak shifts below 400 nm, the nano solution contains other participants such as impurities, organic species, and solvent [37]. The shift in absorption peak may be extremely indicative to size, morphology, quantity, and NPs growth, signifying the current study HAgNP is formed in adequate size and shape.…”
Section: Hagnp Uv-visible Spectroscopic Analysismentioning
confidence: 88%
“…In the present study, there were records of minutes larger than 100 nm and this was also found in previous studies such as [2] they record size of AgNPs between 100-500nm, and [11] founded size of AgNPs in range of 207-293nm. These formed sizes can be explained as due to the capping of nanoparticles by proteins [3,24] , or highly agglomerate nanoparticles resulting in aggregation of nanoparticles during sample preparation [5].…”
Section: Discussionmentioning
confidence: 99%
“…The formation of AgNPs was indicated by the color changed of the solution from pale yellow to dark brown. The formation of these nanoparticles can be tested by spectroscopic and microscopic analysis[5]. The use of biological methods in synthesizing silver nanoparticles using plant extracts is eco-friendly,Journal of Xi'an University of Architecture & Technology Volume XII, Issue III, 2020 Issn No : 1006-7930 low-cost and non-toxic compared with the chemical methods for synthesis of these nanoparticles.…”
mentioning
confidence: 99%